Biology of dengue vectors and their control in Thailand - S. Sucharit (2018)
The vectors of dengue, dengue haemorrhagic fever, and dengue shock syndrome are Aedes aegypti in the urban and rural areas and Aedes albopictus in the rural area. Aedes albolateralis a species member in Aedes niveus subgroup is highly susceptible to dengue 2 virus in laboratory. This species breeds in the forest in bamboo stump and tree hole and may be a source of sylvatic transmission. The anthropophilic, diurnal and domestic habit of Aedes aegypti in the increasing population of the world sustain aegypti population. In South East Asia aegypti is now invading albopictus the original species. Some evidences in biology morphotaxonomy, biochemistry indicate the plasticity of the species. The control strategy mainly for Aedes aegypti are (a) emergency control to interrupt transmission (b) larvicide (c) environmental management. Integrated control would be emphasized. Primary health care aims at extending health services to all the population and participation of each section of the community is essential and under the supervision of vector control professional, making use of the extensive research on vectors and their control.